Increasing of the efficiency of solar batteries use - Romanets, T.; Neymak, V. (Energy and Automation, 2024)
Ways of increasing the efficiency of using solar batteries are being considered. The current state and development trends of renewable energy in Ukraine and the world are analyzed. The share of renewable energy in the energy system has been constantly growing recently. For electricity generation, as well as for heating or desalination, solar energy is becoming increasingly popular around the world. It is one of the fastest growing renewable energy technologies and is playing an increasingly important role in the global energy transformation. Improvements in the technology of obtaining electrical energy from solar radiation lead to the fact that solar energy will eventually become the most available among other alternative sources. In Ukraine, the share of solar generation is the largest among renewable sources and makes up more than half of the installed capacity of all renewable energy. The generation of electrical energy by solar cells varies during the daylight hours. The power output graph is similar to a sine wave. The efficiency of using radiant energy by solar cells depends on their orientation in space. If the generated energy is used exclusively for own consumption, then the effective power and duration of generation do not always coincide with the load schedule. To increase the efficiency of using solar batteries, it is suggested to orient the photovoltaic modules of individual stations, or the photovoltaic modules of individual strings of one station in different azimuth directions. This will allow for a better match between the output schedules and the load, as well as increase the total duration of effective generation. Such a project was implemented during the construction of rooftop solar power plants (SPP) of Khmelnytskyi National University. It was established that the maximum displacement of the power output graphs of SES with an azimuthal angle of +250 and SES with an azimuthal angle of -600 is two hours and 15 minutes. The electricity produced during the daylight hours and the peak power of SES with different azimuthal orientation differ by up to 15 %. The conducted studies allow us to state that when the energy produced by solar batteries is not supplied to the network, but only provides its own consumption, the proposed technical solutions allow expanding the time limits of effective generation and agreeing power output schedules with load schedules.Key words: generation, energy, renewable energy sources, energy efficiency, solar batteries, solar power plant